PENINGKATAN MUTU PENDIDIKAN ISLAM MELALUI PENINGKATAN KREATIFITAS PENDIDIKAN - M Sahibudin M Sahibudin (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2018)
History notes that a country has a high interest in the world of education, and then the country will have a higherexperience progress compared with other countries that subordinate the education problem. Innovation is defined as an idea, practice or object, is considered as something new by an individual, so that innovation can be viewed as an attempt to achieve a certain goal. Education inovation can be spread of some categories; 1) Invention, 2) Development, 3) Diffusion. While the characteristics of educational innovation are 1) Relative advantage, 2) Compatibility, 3) Testability, 4) Observability, 5) Complexity. The five characteristics are the concept maps as follows: 1) Reference advantages, benefits, beneficial user, economical, satisfaction user, 2) Complexity, compicated, and difficulty level, 3) Compatibility, the value of conformity, experience conformity, suitability, 4) Trialability, can be tested, move and fact. 5) Observability, can be observed, seen,and can be felt.